The dynamics of tourism's carbon footprint in Beijing, China. Issue 10 (3rd October 2019) - Yu, Ling; Bai, Yuping; Liu, Jiaming
Abstract: Beijing is an important hub for global tourism, but the extent of tourism's contribution to Beijing's carbon footprint remains unclear. We integrated an environmentally extended multiregional input–output model and the tourism satellite account in a study to estimate the dynamics of Beijing's tourism-related carbon footprint in the post-financial crisis period. Our findings indicate that from 2007 to 2012, whereas the carbon footprint of inbound tourists in Beijing steadily decreased, that of domestic tourists increased. The composition of carbon footprints for the consumption activities of inbound and domestic tourists differed substantially. We also traced the spatial distribution of carbon sources associated with tourism consumption in Beijing. In light of our findings, we offer recommendations to target the adoption of low-carbon consumption patterns by domestic tourists, and energy optimization of service suppliers by increasing energy use efficiency and the renewable energy ratio. In addition, we recommend that public and government should seek to lower energy costs and reduce carbon emissions throughout the life cycle of commodities. We conclude that the government and tourism authorities should actively promote carbon and wider environmental awareness, and that producers must seek to improve the efficiency of their energy use by reducing carbon emissions at source.